2020
DOI: 10.22323/2.19040203
|View full text |Cite
|
Sign up to set email alerts
|

Operationalizing science literacy: an experimental analysis of measurement

Abstract: Inequalities in scientific knowledge are the subject of increasing attention, so how factual science knowledge is measured, and any inconsistencies in said measurement, is extremely relevant to the field of science communication. Different operationalizations of factual science knowledge are used interchangeably in research, potentially resulting in artificially comparable knowledge levels among respondents. Here, we present data from an experiment embedded in an online survey conducted in the United States (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Lastly, the format of the response scale of science literacy may affect the relationship with motivated reasoning. This may be particularly so for recent scales that include metacognitive judgments (definitely true, likely true, etc; McKasy et al, 2020), since metacognition was shown to be comparatively inaccurate for politicized science such as climate change (Fischer et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the format of the response scale of science literacy may affect the relationship with motivated reasoning. This may be particularly so for recent scales that include metacognitive judgments (definitely true, likely true, etc; McKasy et al, 2020), since metacognition was shown to be comparatively inaccurate for politicized science such as climate change (Fischer et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The concept of knowledge, although seemingly straightforward, has been plagued by conceptual disagreement (McKasy et al, 2020). Scholars often distinguish between denotative and connotative knowledge (Graber, 2001).…”
Section: Knowledge Acquisition Across Different Stages Of the Outbreakmentioning
confidence: 99%
“…In this paper, we focus on denotative knowledge by measuring the accuracy of people's recall of number of deadly victims and recoveries from COVID-19. Taking into account that perceived and factual knowledge are oftentimes conflated (Su et al, 2014) and that people tend to overestimate their perceived knowledge (McKasy et al, 2020), factual estimates of consistently reported statistics during the pandemic may, in this case, offer the most valid operationalization of knowledge acquisition.…”
Section: Knowledge Acquisition Across Different Stages Of the Outbreakmentioning
confidence: 99%
See 1 more Smart Citation